2016
DOI: 10.1111/ijd.13199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating serum prolactin and serum dehydroepiandrosterone sulfate levels in patients with pemphigus

Abstract: The patients with pemphigus had higher total and free prolactin and lower DHEAS concentrations, and patients with more severe disease had higher levels of serum total prolactin. These new data may suggest a potential role for sex hormones in the pathogenesis of pemphigus disease and provide new insights for the better management of this chronic and life-threatening disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The role of various cytokines such as leptin (Mozafari, Robati, & Younespour, ) and interleukins 4 (Tavakolpour & Tavakolpour, ), 35 (Tavakolpour et al, ), and 21 (Tavakolpour, ) as well as sex hormones (Yousefi et al, ) and vitamin D (Moravvej, Mozafari, & Younespour, ) in the pathogenesis of pemphigus have also been noted in previous studies .…”
Section: Discussionmentioning
confidence: 62%
“…The role of various cytokines such as leptin (Mozafari, Robati, & Younespour, ) and interleukins 4 (Tavakolpour & Tavakolpour, ), 35 (Tavakolpour et al, ), and 21 (Tavakolpour, ) as well as sex hormones (Yousefi et al, ) and vitamin D (Moravvej, Mozafari, & Younespour, ) in the pathogenesis of pemphigus have also been noted in previous studies .…”
Section: Discussionmentioning
confidence: 62%
“…No statistical difference was noted in between two groups (P>0.05). Yousefi et al 20 found mean serum prolactin level in male patient was 185.4mIU/L and in female patient was 197.5mIU/L. There was no statistical difference between the two groups.…”
Section: Resultsmentioning
confidence: 90%
“…The decline in the concentration of DHEAS is a phenomenon accompanying many autoimmune disorders such assystemic lupus erythematosus (SLE), rheumatoid arthritis (RA), 9 and pemphigus disease. 10 Androgen deficiency especially DHEA and DHEAS have also been reported in many patients with FFA, suggesting a new growing concept of the low androgen level theory in the pathogenesis of FFA. 11 DHEA and DHEAS are the most abundant circulating steroid hormones in humans which have many regulatory effects on the immune system, fat metabolism, and even fibrous pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that serum levels of DHEAS and androstendion were significantly lower in FFA patients compared to controls. The decline in the concentration of DHEAS is a phenomenon accompanying many autoimmune disorders such assystemic lupus erythematosus (SLE), rheumatoid arthritis (RA), 9 and pemphigus disease 10 . Androgen deficiency especially DHEA and DHEAS have also been reported in many patients with FFA, suggesting a new growing concept of the low androgen level theory in the pathogenesis of FFA 11 .…”
Section: Discussionmentioning
confidence: 99%